SINERGISITAS BADAN NARKOTIKA NASIONAL DENGAN KANTOR BEA CUKAI KOTA DUMAI DALAM MENCEGAH PENYELUNDUPAN NARKOBA TAHUN 2021 - Arief Budiman; Zulfa Harirah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The synergy of the customs agency with the national narcotics agency in preventing narcotics smuggling is cooperation in a relationship and institutional or agency setting with a specific division of tasks to produce a good goal, through communication and coordination, therefore the author is interested in further studying the formulation of the problem. "How is the synergy of customs with the Dumai City National Narcotics Agency in preventing drug smuggling" This study aims to find out how the synergy of customs with the Dumai city national narcotics agency in preventing drug smuggling. This research is a type of descriptive research using a quantitative approach. The data collection technique in this study used interview techniques. The data analysis used was interactive quantitative analysis. The results of the study can be concluded that the efforts made by BNN together with Customs and Excise to reduce the number of drug smugglers entering the city of Dumai, as well as eradicate the illicit traffic of narcotics and narcotics precursors, protect and prevent the nation from narcotics abuse. Particularly the National Narcotics Agency and Customs and Excise where the two institutions supervise illegal goods entering Indonesia, especially the Dumai area which is directly opposite neighboring countries. Keywords: Synergy, Communication Techniques and Coordination Techniques